Associations between maximal strength, sprint, and jump height and match physical performance in high-level female football players - Pedersen, S.; Welde, B.; Sagelv, E. H.; Heitmann, K. A.; Randers, M. B.; Johansen, D.; Pettersen, S. A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Studies on females` decisive physical components to physical match-play performance are sparse and only emphasize endurance tests. Thus, the influence of maximal strength and power on physical performance during match-play is currently unknown. The aim of this study was to assess the association between one repetition maximum (1RM) half squat strength, 5-, 10-, and 15-m sprint times, countermovement jump (CMJ) height, and physical high-intensity match-play performance in high-level female football players. Thirty-seven female high-level football players completed 1-2 football matches with physical performance measured by local positioning tracking. Correlations were assessed between physical match-play performance variables (total distance covered, running distance, high-intensity running distance, sprinting distance as well as acceleration and deceleration counts, and peak speed) and laboratory tests (half squat 1RM, 15-m sprint, and CMJ). We found no correlation between 1RM and physical match-play performance. Further, 10-m- and 15-m sprint time (r = -0.56, r = -0.56, p < 0.001) and CMJ jump height (r = 0.50, p < 0.01) strongly correlated with peak match speed. Further, there was a moderate correlation between 15-m sprint time and ACC (r = -0.43, p < 0.05). 5-m sprint time did not correlate with physical match-play performance. Laboratory-based sprint and jump performance, but not maximal half squat strength, showed moderate to large correlations with high-intensity physical match-play performance measures in high-level female football players.